2021
DOI: 10.1039/d1nj01927a
|View full text |Cite
|
Sign up to set email alerts
|

Efficiently selective oxidation of glycerol by BiQDs/BiOBr–Ov: promotion of molecular oxygen activation by Bi quantum dots and oxygen vacancies

Abstract: Selective oxidation of biomass resource glycerol to produce high value-added formic acid, dihydroxyacetone and other fine chemicals are in line with the current development concept of green and sustainable chemistry....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Besides, the other two peaks can be ascribed to different types of chemisorbed O, like –OH and H 2 O. 51 Therefore, we believe that after the PEC HER, the 1% MoS 2 /BiOBr HJ is the only sample able to maintain the original structure with only a small amount of BiOBr reduced to metallic Bi. Indeed it is able to sustain at least 16 cycles of CV under UV light (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Besides, the other two peaks can be ascribed to different types of chemisorbed O, like –OH and H 2 O. 51 Therefore, we believe that after the PEC HER, the 1% MoS 2 /BiOBr HJ is the only sample able to maintain the original structure with only a small amount of BiOBr reduced to metallic Bi. Indeed it is able to sustain at least 16 cycles of CV under UV light (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…), respectively (Figure 1l). 18,23,24 The comparison of the ratio of each oxygen component revealed that NiFe LDH-4 exhibited a higher content of O ads. /H 2 O ads compared with Ni LDH, indicating superior hydrophilic properties.…”
Section: Characterization Of Ni-based Ldh Catalystsmentioning
confidence: 99%
“…In light of the diverse range of selective oxidation products derived from glycerol, Zhang et al reported a study on the oxidation of glycerol to formic acid. [78] They developed BiOBr photocatalysts modified with oxygen vacancies and Bi quantum dots to perform the oxidation of glycerol to formic acid and DHA in an aerobic environment. Remarkably, they achieved a selectivity of 46.2% for formic acid and 26.9% for DHA, with a glycerol Figure 17.…”
Section: Selective Oxidation Of Glycerolmentioning
confidence: 99%